Design of ultra wideband isolation of RF switch for microwave imaging in medical application - Mohd Sanusi, Nursyahirah (2021)
Microwave imaging is an emerging technology in the medical application similar to that of other technologies, such as X-ray, Magnetic Resonance Imaging (MRI), and Computed Tomography scan (CT scan). In designing a microwave imaging system for medical application, it can use a monostatic radar approach by transmitting a Gaussian pulse (with an ultra wideband (UWB) frequency) through several antennas. RF switches are designed to control the transmit and receive operations of the antennas in the microwave imaging system. However, there will be RF leakages to another unused antennas, thus ultra wideband isolation performance is essential in RF switch design to avoid any signal power leakage between antenna ports during transmit and receive signal operations. The circuit topology was studied to achieved UWB isolation performance for microwave imaging. The fabrication technology PIN diodes was investigate using silicon PIN diodes and silicon glass PIN diodes. The result of S-parameter was analyze in term of return loss, insertion loss and isolation. Therefore, in this research work, two techniques were chosen for further investigation and study for ultra wideband isolation performance of RF switch; they are RF switch topology and fabrication technology of PIN diode. Four different RF switch topologies were investigated in a single pole double throw (SPDT) switch. Concurrently, in the same SPDT switch circuit, two fabrication technologies of PIN diode were selected and investigated as well. They are silicon PIN diodes (from Skyworks Solutions) and silicon glass PIN diodes (from MACOM Technology Solutions). The best RF switch topology in SPDT switch was then selected and used in a single pole eight throw (SP8T) switch, which is a final RF switch design for the front end system of microwave imaging. As result, first, series-shunt-shunt is the best RF switch topology for ultra wideband isolation performance compared to other topologies. It was selected after considering other trade off such as return loss and insertion loss performances. Second, in the fabrication technology of PIN diodes, it was found that the silicon glass PIN diode (MACOM) gave the best isolation compared to silicon PIN diode (Skyworks). In the simulated result, the final design of the RF switch (SP8T) produced 9.3 GHz of isolation bandwidth that can be used for Gaussian pulse bandwidth up to 9.3 GHz (from 1.7 GHz to 11 GHz frequency spectrum). Thus, by combining these two techniques; the series-shunt-shunt topology and silicon glass PIN diode gave the best ultra wideband isolation of RF switch for microwave imaging in medical applications.